Pelatihan Pemanfaatan Barang Bekas sebagai Media Pembelajaran di Taman Kanak-Kanak - Mohammad Dani Wahyudi; Celia Cinantya; Maimunah Maimunah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The problem in this community service activity is the use of learning media that is less varied. This is because most teachers are less creative in utilizing the objects around them as innovative learning media. Therefore, the solution used to overcome this problem is to carry out workshops on using used goods as learning media in Kindergarten. This activity aims to provide insight and skills to teachers at partner schools to use used materials around them in exciting learning media. This Community Service activity was conducted at the Pembina State Kindergarten, East Banjarmasin District, Banjarmasin City. The method used in this activity is a lecture, demonstration, and question and answer method. All teachers in the school participated in this activity. This training activity results in teachers gaining knowledge and skills in utilizing used goods in the surrounding environment in exciting and innovative learning media.